Elemental discourses - Sallis, John C. 1938- (Indiana University Press, 2018)
Voices -- Gathering language -- The play of translation -- Things of sense -- Archaic nature -- Alterity and the elemental -- Objectivity and the reach of Enchorial space -- The scope of visibility -- Cosmic time -- The negativity of time-space
Includes bibliographical references and index
Keywords: Philosophie; Philosophy, American / 20th century; Aufsatzsammlung